Minilaparotomy Hysterectomy as a Suitable Choice of Hysterectomy for Large Myoma Uteri: Literature Review - Kenichiro Sato; Yasuyoshi Fukushima (Hindawi Limited, 2016)
The objective of this paper is to propose minilaparotomy hysterectomy as the suitable choice for large uterus on the basis of our experienced case of performed minilaparotomy hysterectomy to 4,500 g myoma uteri and review published cases about this clinical condition. We presented a 44-year-old woman (gravida 0, virgin) who consulted our hospital because of the chief complaints of abnormal genital bleeding and hypermenorrhea. Transabdominal ultrasonography revealed that abdominal solid tumor reached over the navel. Her tumor was an indication of surgery; to do minilaparotomy hysterectomy with laparoscope was decided because her informed consent was obtained. A 6 cm transverse incision (Maylard incision) was made to the skin above the pubic hairline. At the end of surgery, the length of abdominal wound was 8.5 cm, operating time was 128 min, weight of resected myoma uteri was 4,500 g, and intraoperative blood loss was 895 mL. Blood transfusion was not done; postsurgical course was not a problem without anemia. We propose that a large uterine case in which it is difficult to perform vaginal or laparoscopic hysterectomy should be considered in order to select minilaparotomy hysterectomy up to around 5 kg weight of uterus, and the length of skin incision in minilaparotomy hysterectomy is necessarily <9 cm particularly in large uterus.